Lactylation-mediated miRNA regulation in cancer therapy resistance - Yiyi Shou; Ruiqi Liu; Hao Xiong; Xiaoyan Chen; Luanluan Huang; Ran Huang; Hailong Sheng; Haibo Zhang; Yanwei Lu; Haiwei Guo (Journal of Translational Medicine)
Abstract Therapeutic resistance in cancer is increasingly understood as a dynamic outcome of the interplay among tumour metabolism, epigenetic regulation, and immune modulation, rather than a consequence of genetic mutations alone. At this intersection, lactylation-a recently discovered lactate-derived post-translational modification (PTM)-acts as a molecular bridge linking metabolic rewiring to transcriptional and post-transcriptional control. Meanwhile, microRNAs (miRNAs) have emerged as essential regulators of metabolic adaptation and epigenetic plasticity. However, the interaction between lactylation and miRNA networks remains largely underexplored. Herein, we present a comprehensive and structured assessment of this emerging interdisciplinary field. We begin with a focused overview of tumour metabolic reprogramming and the enzymology of lactylation, establishing the biochemical context for its regulatory functions. We then examine how miRNAs interpret and reinforce metabolic cues, particularly through three interrelated regulatory frameworks. Lactylation of histones and DNA repair proteins has been shown to activate oncogenic miRNA clusters; these same miRNAs, in turn, enhance glycolytic flux and fine-tune the activity of lactylation enzymes, forming bidirectional feedback loops. Under stress conditions such as hypoxia or chemotherapy, lactate accumulation selectively suppresses DNA-repair-targeting and Pro-apoptotic miRNAs, stabilising BRCA1/RAD51-mediated repair programs. Furthermore, lactylation-dependent miRNA signals disseminate via extracellular vesicles, contributing to T cell exhaustion and macrophage M2 polarisation, thus shaping an immunosuppressive tumour microenvironment. Based on these converging mechanisms, we highlight potential therapeutic strategies, including the co-targeting of LDHA and oncogenic miRNAs (e.g., nanoparticle-mediated delivery of anti-miR-21), as well as liquid biopsy-based monitoring of circulating H3K18la and miRNA signatures to predict emerging resistance. By integrating metabolic, epigenetic, and immunologic perspectives, we position lactylation-miRNA crosstalk as a central regulatory axis in cancer therapy resistance and offer a conceptual framework to inform the development of future mechanism-driven interventions.